Dietary intake of broiler breeder hens during the laying period affects amino acid and fatty acid profiles in eggs - Li,Feng (2019)
ABSTRACT The objective of this study was to evaluate the effects of maternal dietary intake on the amino acid and fatty acid contents in eggs during the laying period. An experiment with a 2×2 factorial design was conducted with two maternal dietary intake levels (100 and 75% of dietary intake recommended by the Chinese Ministry of Agriculture) and two broiler lines (fat and lean line). A total of 384 hens of fat line and 384 hens of lean line at 23 weeks of age were included in the experiment. Each line was randomly divided into two treatments (n = 192 in each treatment, with 12 replications), and each replication included 16 birds. The treatments were LN (lean line and normal maternal dietary intake, n = 192), LL (lean line and low maternal dietary intake, n = 192), FN (fat line and normal maternal dietary intake, n = 192), and FL (fat line and low maternal dietary intake, n = 192). The amino acid and fatty acid contents in eggs were tested (50 weeks of age). The fat line had higher levels of arginine, aspartic acid, glycine, histidine, leucine, methionine, and threonine in the egg albumen than the lean line. Low maternal dietary intake increased the cystine deposition in egg yolks. There were interactions between maternal dietary intake and line on the deposition of trans-oleic acid, docosanoic acid, and total fatty acid in egg yolks. Low maternal dietary intake increased the deposition of tetradecenoic and linolenic acids and the ratio of total polyunsaturated fatty acids to total saturated fatty acid in egg yolks but decreased the deposition of docosanoic acid. Maternal dietary intake and line affect the amino acid and fatty acid profiles in eggs.